Komunitas Merek Digital dalam Sepak Bola Indonesia: Analisis Isi Interaksi Penggemar Persib Bandung di Media Sosial - Ridha Handayani; Asep Kurnia Saputra; Edison Bonartua Hutapea (Universitas Palangka Raya, 2026)
This study analyzes the formation of a digital brand community through Persib Bandung fan interactions on social media. The research aims to examine how content distribution, message functions, and engagement patterns contribute to the construction of collective identity and digital rituals among supporters. Using a qualitative-interpretative content analysis supported by quantitative descriptive data, this study analyzes 418 posts published on Persib Bandung's official Instagram, TikTok, Facebook, X/Twitter, and YouTube accounts from November 27 to December 10, 2025. The findings reveal that Persib Bandung generated 29,543,663 total interactions, with Instagram and TikTok emerging as the most affective platforms for engagement. Non-match content (41.4%) and emotional or motivational messages (40.2%) dominate communication. Despite high public engagement, no evidence of two-way talkback from the official account was found, indicating a predominantly one-way communication model. The study concludes that Bobotoh function as a digital brand community characterized by collective identity, digital rituals, loyalty, symbolic ownership, and co-creation of brand meaning through measurable public interactions. This research contributes to the understanding of sports communication and digital brand communities in emerging football markets.